Methodology for stakeholders’ consultation (participatory actions) [construction and demolition waste management] - Ramos, Mário (2021)
This report outlines the methodological approach used in the participatory process to improve construction and demolition waste (CDW) management in the Baixo Alentejo region of Portugal. This process involved collaboration with municipal technicians and representatives from micro and small construction companies.